Physics : Volumen 2 : Electricity and Magnetism and Optics - Reimann, Arnold L (International textbook series)
Contenido . v.1. Mechanics and heat. -- v.2. electricity magnetism and optics. -- Incluye respuestas de problemas seleccionados e índice